2020
DOI: 10.3846/jcem.2020.13810
|View full text |Cite
|
Sign up to set email alerts
|

Physical Parameters, Tensile and Compressive Strength of Dolomite Rock Samples: Influence of Grain Size

Abstract: The purpose of this paper is to investigate the strength, physical and engineering index parameters of selected dolomitic rocks with emphasis on grain size. For this purpose, three groups of dolomite from north western Iran, with the same mineral composition but different grain size, were selected; fine grain, medium grain and coarse grain. Three sets of laboratory experiments are performed on 32 samples: first; petrography tests for determining mineral composition and their percentage, and microstructure of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…For instance, between temperatures of 25 a 400 °C (Figure 9a-c), both the load and the duration of acoustic emissions remained belo 275 s. It was only at a temperature of 600 °C that the samples experienced failure at a proximately 270 s, with the peak displacement being more than double that at other te peratures. This is primarily due to a series of activities in the granite, such as therm expansion, dehydration, thermal decomposition, and phase transformation at 600 °C, w the most representative being the phase transition of α-quartz to β-quartz at 573 [14,63,64]. These activities disrupt the rock's native framework, increase the spacing b tween mineral grains, and promote the development of secondary defects, thereby redu ing the brittleness and increasing the ductility of the samples.…”
Section: Brazilian Test Mechanics and Acoustic Emission Patternsmentioning
confidence: 99%
“…For instance, between temperatures of 25 a 400 °C (Figure 9a-c), both the load and the duration of acoustic emissions remained belo 275 s. It was only at a temperature of 600 °C that the samples experienced failure at a proximately 270 s, with the peak displacement being more than double that at other te peratures. This is primarily due to a series of activities in the granite, such as therm expansion, dehydration, thermal decomposition, and phase transformation at 600 °C, w the most representative being the phase transition of α-quartz to β-quartz at 573 [14,63,64]. These activities disrupt the rock's native framework, increase the spacing b tween mineral grains, and promote the development of secondary defects, thereby redu ing the brittleness and increasing the ductility of the samples.…”
Section: Brazilian Test Mechanics and Acoustic Emission Patternsmentioning
confidence: 99%
“…Many microscale factors affect the macroscopic mechanical properties of rocks. Lakirouhani et al [6,7] conducted uniaxial compression and Brazilian splitting tests on rocks, and they found that the macroscopic strength and Young's modulus of rocks exhibit a positive correlation with their grain size and a negative correlation with their quartz mineral content. With advancements in nondestructive testing technology, it has become feasible to study rock damage evolution from a microscopic structural perspective [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yu [22] found that grain size resulted in different stress concentrations within a rock; the bigger the grain size was, the stronger the stress concentration was, and the lower the rock strength was. Lakirouhani [23] concluded that there was a significant positive correlation between grain size and tensile strength.…”
Section: Introductionmentioning
confidence: 99%